Investigation of possibilities for high heavy metal content sludges utilization by incorporating them in concrete products - Simeonova A.; Petkov A.; Delchev N.; Balgaranova J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The safe removal of sludge, obtained during the surface treatment of different metal products, is a serious environmental problem. These sludges are usually characterized by a high content of heavy metals (Pb, Cu, Ni, Zn, Cr, Cd, Mn), low quality and are obtained in many small industrial units in the whole country, which makes their centralized treatment difficult. In world practice, different methods are used for component fixation of such sludge, in the aim to prevent leaching of the metals causing pollution of the soil and underground water. The aim of the recent work is to prepare the sludge in a form of light (keramzit) fillers by preliminary treatment with binding substances and to introduce them in non supporting concrete products - curbs, stakes and similar products. The investigation was made with two types of sludge - from a production line for thermal treatment and hardening of different parts used in machine building and from a production line for surface decoration treatment (nickel-plating and chromium-plating) of consumer products. The sludge were dried and ground and then granulated with a solution of water glass. After their solidifying the air dried granules with a size of 5 to 15 mm were treated with cement milk and air dried again. With the obtained granules, standard percolation test for leaching metals like Pb, Cu, Zn, Ni and Cr was carried out. After a preliminary calculation of concrete mixtures, these granules were mixed with Portland cement and concrete sample products were made. These molded concrete samples were characterized by their density, water absorption, and mechanical strength for defined standard periods of time. The samples were subjected to a modified percolation test for leaching metals. The metal concentration in eluates was determined by Atomic Spectral Analysis.